0.33333333333(6y-9)=-2y+13

Simple and best practice solution for 0.33333333333(6y-9)=-2y+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.33333333333(6y-9)=-2y+13 equation:


Simplifying
0.33333333333(6y + -9) = -2y + 13

Reorder the terms:
0.33333333333(-9 + 6y) = -2y + 13
(-9 * 0.33333333333 + 6y * 0.33333333333) = -2y + 13
(-3 + 2y) = -2y + 13

Reorder the terms:
-3 + 2y = 13 + -2y

Solving
-3 + 2y = 13 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
-3 + 2y + 2y = 13 + -2y + 2y

Combine like terms: 2y + 2y = 4y
-3 + 4y = 13 + -2y + 2y

Combine like terms: -2y + 2y = 0
-3 + 4y = 13 + 0
-3 + 4y = 13

Add '3' to each side of the equation.
-3 + 3 + 4y = 13 + 3

Combine like terms: -3 + 3 = 0
0 + 4y = 13 + 3
4y = 13 + 3

Combine like terms: 13 + 3 = 16
4y = 16

Divide each side by '4'.
y = 4

Simplifying
y = 4

See similar equations:

| 80=2(n+6) | | -3.3=4.7-4y | | 6/(2a) | | .30=x(.14)+(1-x)(.05) | | 4x-11=15-9x | | -10500x^3+5000=0 | | 6+5z=8+5z | | 102x^2+6y^2+89y-322=0 | | 55x-39x+12=-64 | | -4=-2(5n-2)-8(-7n+1) | | 28-2x=3x+18 | | .03=.14x+.05-05x | | 8+.09m=90 | | G(2)=5-7+2 | | b/0.8=12.6 | | -6m-13=74 | | 6x^2-54x/x-9•7x/6x | | -7.1=2.9-5y | | 10=1.25*p | | g/3.2=4.7 | | g/2=0.5 | | 4r^2=34-10r | | 4(24)=4(20)+4(4) | | (5x+7)+(4x-18)+(3x+2)=x | | 4q+8q+7q-7= | | 9x+x=79 | | 2(6k-7)+6(-3k+1)=22 | | 175+g=118 | | 4y=3(y-5)-2 | | 4(24)=4(20+4(4)) | | 4=0.25(w-4/3) | | 5x+7+4x-18+3x+2=x |

Equations solver categories